Terahertz Generation through Coherent Excitation of Slow Surface Waves in an Array of Carbon Nanotubes - Sergey A. Afanas’ev; Andrei A. Fotiadi; Aleksei S. Kadochkin; Evgeny P. Kitsyuk; Sergey G. Moiseev; Dmitry G. Sannikov; Vyacheslav V. Svetukhin; Yury P. Shaman; Igor O. Zolotovskii (Photonics, 2023)
In this paper, we present a scheme for generating terahertz (THz) radiation using an array of parallel double-walled carbon nanotubes (DWCNTs) subjected to a direct current (DC). The longitudinal surface plasmon polaritons (SPPs) in the DWCNTs are coherently excited by two near-infrared laser beams with slightly different frequencies. Through numerical methods, we investigate the spectral characteristics of the SPPs in the presence of a DC current in the nanotubes. We identify high-quality plasmonic modes with a slowdown factor exceeding 300 in the terahertz frequency region. The amplification of these slow SPP modes is facilitated by the DC current in the DWCNTs, fulfilling a synchronism condition. This condition ensures that the phase velocity of the SPPs is closely matched to the drift velocity of the charge carriers, allowing for an efficient energy exchange between the current and the surface electromagnetic wave. The high-frequency currents on the nanotube walls in the DWCNT array enable the emission of THz radiation into the far field, owing to an antenna effect.